2014
DOI: 10.1093/cvr/cvu224
|View full text |Cite
|
Sign up to set email alerts
|

The role of the FPR2/ALX receptor in atherosclerosis development and plaque stability

Abstract: AimsThe formyl peptide receptor (FPR) subtype FPR2/ALX transduces pro-inflammatory responses and participates in the resolution of inflammation depending on activation. The aim of the present study was to unravel the role of FPR2/ALX signalling in atherosclerosis.Methods and resultsExpression of FPR2/ALX was analysed in 127 human carotid atherosclerotic lesions and revealed that this receptor was expressed on macrophages, smooth muscle cells (SMCs), and endothelial cells. Furthermore, FPR2/ALX mRNA levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
112
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 44 publications
8
112
0
Order By: Relevance
“…Both the BLT 1 receptor [4] and FPR2/ALX [5] are expressed in several cell types within human atherosclerotic plaques, such as macrophages, vascular smooth muscle cells (SMC), and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the BLT 1 receptor [4] and FPR2/ALX [5] are expressed in several cell types within human atherosclerotic plaques, such as macrophages, vascular smooth muscle cells (SMC), and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, knock-out of the mouse homologue of the human FPR2/ALX receptor exacerbates mesentery ischemia-reperfusion, paw edema and arthritis [8]. However, in other murine disease models, such as OVA/alum-induced allergic airway inflammation and atherosclerosis [5], FPR2/ALX deficiency is associated with reduced disease and cytokines levels [5,9]. In contrast, protective effects of BLT 1 receptor deficiency has been replicated in several inflammatory mouse models, such as atherosclerosis, abdominal aortic aneurysms and arthritis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LXs modulate plateletderived growth factor-stimulated migration of vascular SMCs isolated from human saphenous veins [66]. Interestingly, the pluripotent FPR2/ALX receptor may play a dual role in atherosclerosis, promoting disease progression through proatherogenic effects on bone marrow-derived cells, but increasing plaque stability by promoting SMC collagen synthesis and cross-linking [104]. In this context, it is worth highlighting that the characteristic expression of SMC and MΦ surface markers may be altered in the pathophysiological milieu of the atherosclerotic plaque so that MΦs may express SMC markers (e.g.…”
Section: Lipoxins In Atherosclerosis and Cardiovascular Diseasementioning
confidence: 99%
“…It has also been demonstrated that ECs apoptosis induced atherosclerotic lesion development and plaque shedding [3][4][5]. Oxidized Low-Density Lipoprotein (ox-LDL), an important atherosclerotic risk factor, may induce ECs apoptosis during the pathogenesis of AS [6][7][8].…”
Section: Introductionmentioning
confidence: 99%